Structural performance of textile reinforced concrete sandwich panels under axial and transverse load - Hong Junqing (De Gruyter, 2021)
The performance of textile reinforced concrete composite panels (TRCCPs) under the action of pseudo-static load up to collapse was evaluated. The test of TRCCPs under axial and transverse loading was conducted, and the results were compared with those for steel wire mesh reinforced-concrete composite panels (SMRCCPs). Ceram-site concrete was utilized as the panel matrix owing to its lightweight and insulation characteristics. The ultimate load bearing capacity, load-deformation and load-strain relationships, and failure modes were discussed and investigated in comparison with the findings of non-linear finite-element-model (FEM) analysis and the analytic method on the basis of the reinforced concrete (RC) theory. The analysis results indicate that TRCCP is suitable for use as a potential structural member for a wall or slab system of buildings, and the typical RC theory can be applied to predict the ultimate load bearing capacity if modified suitably.